Successful use of cytarabine and bendamustine in a patient with mantle cell lymphoma and acute renal failure using intermittent hemodialysis: A case report. (April 2019) - Ettleson, Matthew; Bongers, Kale S; Vitale, Kaitlyn; Perissinotti, Anthony J.; Phillips, Tycel; Marini, Bernard L.
Mantle cell lymphoma is a mature B-cell non-Hodgkin lymphoma characterized by the hallmark (11;14) chromosomal translocation, which often presents with lymphadenopathy and extra-nodal involvement. Young, fit patients are generally treated with chemotherapy approaches that incorporate high-dose cytarabine (e.g. the Nordic regimen) followed by autologous hematopoietic cell transplantation. Because of the significant activity of cytarabine in mantle cell lymphoma, increasingly, high- and intermediate-dose cytarabine are being used in the treatment of elderly mantle cell lymphoma patients. In practice, many patients present with significant organ dysfunction and there is limited data on the use of high- to intermediate-dose cytarabine and bendamustine in this setting. Here, we report a case of a critically ill, elderly patient with mantle cell lymphoma and concomitant acute kidney injury and oliguria who was successfully treated with a cycle of cytarabine (Ara-C) and bendamustine accompanied by intermittent hemodialysis.